Early experience of pump-controlled retrograde trial off for weaning from veno-arterial extracorporeal membrane oxygenation in adult patients with cardiogenic shock. (May 2021) - Ju, Min Ho; Lim, Mi Hee; Lee, Soo Yong; Lee, Chee-Hoon; Je, Hyung Gon
Introduction: Pump-controlled retrograde trial off has recently been introduced as an effective method for weaning from veno-arterial extracorporeal membrane oxygenation in pediatric patients. However, studies on pump-controlled retrograde trial off in adults are still lacking. Thus, this study aimed to examine the outcomes of pump-controlled retrograde trial off for weaning from veno-arterial extracorporeal membrane oxygenation in adult patients. Methods: Between January 2018 and July 2019, 87 consecutive adult patients underwent veno-arterial extracorporeal membrane oxygenation support, of whom 47 (54.0%) underwent pump-controlled retrograde trial off for weaning from extracorporeal membrane oxygenation and were enrolled in this study. The pump-controlled retrograde trial off results, extracorporeal membrane oxygenation reapplication rate, and clinical outcomes were analyzed. Results: Of the 47 patients, 38 (80.9%) were weaned from veno-arterial extracorporeal membrane oxygenation on the first attempt of pump-controlled retrograde trial off, 5 (10.6%) on the second attempt, and 4 (8.5%) on the third attempt. Three patients were converted to venovenous extracorporeal membrane oxygenation by desaturation but had stable blood pressure during pump-controlled retrograde trial off. No extracorporeal membrane oxygenation reapplication was performed within 3 days after removal, and two patients underwent veno-arterial extracorporeal membrane oxygenation during follow-up. No complications associated with pump-controlled retrograde trial off occurred during the weaning process, including thromboembolic events. Five in-hospital deaths (10.6%) occurred after weaning from extracorporeal membrane oxygenation. Conclusion: Pump-controlled retrograde trial off is an effective method to safely wean from veno-arterial extracorporeal membrane oxygenation in adult patients. It is simple and can be easily implemented without additional invasive procedures and may help prevent deterioration of the cardiovascular system after weaning from veno-arterial extracorporeal membrane oxygenation.